Role of sustainability in buying decision-making on strategic software in Finnish SMEs - Joronen, Mari (My University, 2024)
This research focuses on the role of sustainability on strategic software buying decision-making in SMEs operating in Finland from Gen-Z and Millennial decision-makers point of view. As the generations of organizational buying decision-makers and therefore the ways to do business have changed, the aim of this study is to understand the role of sustainability as part of the strategic software buying decision-making among the organizational decision-makers in SMEs operating in Finland. The study was conducted by interviewing Gen-Z and Millennial decision-makers in various companies using semi-structured interview approach about their experiences on decision-making on strategic software. First evolution of organizational buying decision-making is discussed, then the elements in buying strategic software are discovered and finally the role of sustainability on strategic buying decision-making in SMEs is studied. Sustainability’s role in the new era of buying decision-making on strategic software is recognized and understood as an increasingly important factor among the new generation of decision-makers. As sustainability becomes more integrated into business strategies and stakeholder demands grow, its role in buying decision-making for strategic software is likely to become more pronounced. However, it is currently seen an emerging rather than dominant factor in strategic software buying decision-making among the interviewed SME companies’ decision-makers. This research indicated that the sustainability’s role in buying decision-making on strategic software in SMEs is an indirect force that is impacting the buying decision-making through individual decision-makers personal values, stakeholder demands, companies own values, through socio-cultural change and through creating trust among the customers, which all are impacting decision-making on strategic software in different stages of buying decision-journey. Concluding all this sustainability characterizes the new era of organizational buying decision-making as an emerging consideration, with vendor companies generally assumed to be sustainable, though further research on vendor backgrounds is common. As sustainability is becoming more important factor in buying decision-making on strategic software, vendor companies should communicate their efforts or their offerings capabilities promoting sustainability in their digital channels, as the research found out and as it is already stated in theory that 60% of the buying journey takes place on information gathering.

Tässä tutkimuksessa tutkitaan vastuullisuuden merkitystä strategisten ohjelmistojen päätöksenteossa Suomessa toimivissa pk-yrityksissä Gen-Z- ja Milleniaali-päättäjien näkökulmasta. Koska yritysten päätöksentekijät edustavat yhä nuorempia sukupolvia, myös tavat tehdä liiketoimintaa ovat muuttuneet. Tämän tutkimuksen tavoitteena on ymmärtää vastuullisuuden roolia osana strategista ohjelmistopäätöksentekoa Suomessa toimivien pk-yritysten uuden sukupolven organisaatiopäättäjien keskuudessa. Tutkimukseen haastateltiin strategisista ohjelmistoista päättäviä Gen-Z- ja Milleniaali-päätöksentekijöitä eri alan yrityksistä puolistrukturoitua haastattelumenetelmää käyttäen. Päätöksentekijöitä haastateltiin heidän kokemuksistaan strategisten ohjelmistojen päätöksenteossa ja siitä minkälainen merkitys vastuullisuudella oli päätöksentekoon. Tutkimus keskittyy ensin siihen, miten organisaatiopäätöksenteko on kehittynyt aikojen saatossa, jonka jälkeen siinä avataan strategisten ohjelmistojen ostamiseen liittyviä elementtejä. Tämän jälkeen tutkimus keskittyy tutkimaan vastuullisuuden merkitystä strategisten ohjelmistojen päätöksenteossa pk-yrityksissä. Tutkimuksesta selviää kuinka uuden sukupolven päätöksentekijät tunnistavat ja ymmärtävät vastuullisuuden yhä tärkeämmäksi tekijäksi strategisten ohjelmistojen päätöksenteossa. Kuitenkin vastuullisuus on kuitenkin pikemminkin nouseva kuin hallitseva tekijä tämänhetkisessä päätöksenteossa strategisista ohjelmistoista puhuttaessa haastateltujen päätöksentekijöiden mielestä. Näin ollen, vastuullisuudella nähtiin olevan epäsuora vaikutus pk-yritysten strategisten ohjelmistojen päätöksenteossa. Vaikutus nähtiin olevan epäsuora, sillä sen nähtiin tulevan epäsuorista lähteistä kuten yksittäisten päätöksentekijöiden henkilökohtaisista arvoista, eri sidosryhmien vaatimuksista, yritysten omista arvoista ja sosiokulttuurisesta muutoksesta ja luottamuksen luomisesta. Vaikka vastuullisuuden merkitys on vasta korostumassa, uuden sukupolvien päättäjien näkökulmasta ohjelmistoja myyvien yritysten oletetaan olevan vastuullisia, vaikka myyjäyritysten taustat yleensä tutkitaan. Koska vastuullisuudesta on tulossa yhä tärkeämpi tekijä strategisia ohjelmistoja koskevassa päätöksenteossa, myyjäyritysten kannattaa tuoda esiin vastuullisuusasiat sen erilaisissa digitaalisissa kanavissa, sillä organisaatio ostaminen on yhä itsenäisempää ja digitaalisempaa.
Keywords: B2B, buying behaviour, buying decision-making, strategic software purchase, Gen-z, Millennials, SMEs, B2B, ostoskäyttäytyminen, ostopäätöksenteko, strategisen ohjelmiston ostaminen, Gen-Z, Milleniaalit, pienet ja keskisuuret yritykset